Nanophotonic structures and materials - Andrews, David L., 1952- (Photonics, 2015)
Nanophotonics is photonic science and technology that utilizes light/matter interactions on the nanoscale where researchers are discovering new phenomena and developing techniques that go well beyond what is possible with conventional photonics and electronics. The topics discussed in this volume are: cavity photonics; cold atoms and Bose-Einstein condensates; displays; e-paper; graphene; integrated photonics; liquid crystals; metamaterials; micro-and nanostructure fabrication; nanomaterials; nanotubes; plasmonics; quantum dots; spintronics; thin film optics. Written for the graduate level student in physical sciences, industrial and academic researchers in photonics, policymakers, consultants, scientific and technical libraries, government laboratories, and NIH. --